Driving Firm Value Through Sustainability: The Role of Carbon Emission Disclosure, Eco-Efficiency, and Green Innovation in Indonesian Energy Companies - Fidya Ayundira; Veronika Santi Paramita (Indonesian Scientific Publication, 2026)
This study examines the effects of eco-efficiency, green innovation, and carbon emission disclosure on firm value among energy companies listed on the Indonesia Stock Exchange during 2020–2024. A quantitative panel data approach was employed using secondary data obtained from annual financial reports and sustainability reports. The final sample consisted of 16 energy companies with 5 years of observation, resulting in 80 company-year observations. Panel data regression analysis was applied to investigate the causal relationships among the study variables. Carbon emission disclosure was calculated using GRI 305. The empirical results indicate that green innovation has a positive and significant impact on firm value. Conversely, carbon emission disclosure has a negative impact on firm value. Meanwhile, ecological efficiency does not show a significant impact on firm value. Overall, the findings suggest that Indonesian investors place greater emphasis on innovation-oriented sustainability strategies rather than solely on efficiency- or compliance-based environmental measures when evaluating firm value in the energy sector.